Macroeconomics : an introduction - Alex M Thomas (New York Cambridge University, 2024)
Macroeconomics: An Introduction, provides a lucid and novel introduction to macroeconomic issues. It introduces the reader to an alternative approach of understanding macroeconomics, which is inspired by the works of Adam Smith, David Ricardo, Karl Marx, John Maynard Keynes, and Piero Sraffa. It also presents the reader with a critical account of mainstream marginalist macroeconomics. The book begins with a brief history of economic theories and then takes the reader through three different ways of conceptualizing the macroeconomy. Subsequently, the theories of money and interest rates, output and employment levels, and economic growth are discussed. The book ends by providing a policy template for addressing the macroeconomic concerns of unemployment and inflation. The conceptual discussion in Macroeconomics is situated within the context of the Indian economy. Besides using publicly available data, the contextual description is instantiated using excerpts from works of fiction by Indian authors.
Keywords: Macroeconomics